Os consórcios públicos no planejamento e gestão regionalizada do território brasileiro: as experiências mineiras do COM10 e CODAP - Guilherme Pereira de Vargas (2012)
The Federal Constitution of 1988 reformed the organization of the Brazilian state. In the axis of the democratization of the country, one of the main points of discussion concerned the need for decentralization of power highly concentrated in the Union. Thus a complex process ofredistribution of functions and powers was established with the transfer of important public policy for the lower subnational levels. The municipalities were the main entities affected, having to cope with a series of new issues that they were not prepared to deal with. In thiscontext, the use of consortiums between federate entities for the provision of certain public policies was intensified. The aim of this dissertation is to discuss the consequences and analyze the possibilities and limitations of public consortiuns under Brazilian federate structure. To illustrate this debate two experiences occurring in the state of Minas Gerais are discussed: the COM10, in the northern portion of the Metropolitan Region of Belo Horizonte - RMBH - and the CODAP, located in the central region of the state. These initiatives gave elements of analysis for the debate of these form of association that may have broad regional and territorial implications. These reflections are expected to contribute to the betterdevelopment of consortia initiatives, and consequently planning and management of public policies at the regional level.